Integrating nested PCR with high-throughput sequencing to characterize mutations of HBV genome in low viral load samples. Issue 30 (July 2017) - Wang, Xianjun; Xu, Lihui; Chen, Yueming; Liu, Anbing; Wang, Liqian; Xu, Peisong; Liu, Yunhui; Li, Lei; Meng, Fei
Abstract : Abstract: Due to the low viral load of hepatitis B virus (HBV) in plasma samples, conventional techniques have limitations to the detection of antiviral resistance mutations. To solve the problem, we developed a fast, highly sensitive, and accurate method to sequence the HBV whole-genome sequencing in plasma samples which had various viral loads from very low to high. Twenty-one plasma samples were collected from patients who were carriers of HBV from the Hangzhou First People's Hospital. Two pairs of conserved, overlapping, nested primers were used to amplify and sequence the whole HBV genome in 8 plasma samples with different viral loads. High-throughput sequencing was performed on Illumina MiSeq platform. Concomitantly, 3 samples were directly sequenced without PCR amplification. We compared amplicon-sequencing with direct sequencing to develop a method for amplifying and characterizing the whole genome of HBV. HBV genome was amplified from all samples and verified by Sanger sequencing, regardless of the viral loads. Sequencing results revealed that only a few reads were mapped to the HBV genome following direct sequencing, while the amplicon-sequencing reads had a good coverage and depth. We identified 50 intrahost single nucleotide variations (iSNVs), 14 of which were low frequency mutations. Interestingly, iSNVs were more common in low viral load samples than in high viral load samples, and mutations in the reverse transcriptase (RT) region were most prevalent. We conclude that amplicon-sequencing is not only a practical method to detect HBV infection with a high sensitivity and accuracy but also enables to detect mutations in the HBV genome in low viral load samples from HBV-infected patients. Thus, our findings provide a new diagnosis method of HBV infection, which is capable of detection of low frequent mutations in low viral load samples.